Universal Architectural Concepts Underlying Protein Folding Patterns - Konagurthu, Arun S.; Subramanian, Ramanan; Allison, Lloyd; Abramson, David; Stuckey, Peter J.; Garcia de la Banda, Maria; Lesk, Arthur M. (Frontiers in Molecular Biosciences, 2021)
What is the architectural ‘basis set’ of the observed universe of protein structures? Using information-theoretic inference, we answer this question with a comprehensive dictionary of 1,493 substructures – called concepts – at a sub-domain level, based on an unbiased subset of known protein structures. Each concept represents a topologically-conserved assembly of helices and strands that make contact. Any protein structure can be dissected into instances of concepts from this dictionary. We dissected the Protein Data Bank and completely inventoried all concept instances. This yields many insights, including: correlations between concepts and catalytic activities or binding sites, useful for rational drug design; local amino-acid sequence–structure correlations, useful for ab initio structure prediction methods; and information supporting the recognition and exploration of evolutionary relationships, useful for structural studies. An interactive site, PROÇODIC, at http://lcb.infotech.monash.edu.au/prosodic provides access to and navigation of the entire dictionary of concepts, and all associated information.